Compliance behavior with Indonesian language in local government administration: An analysis of the Rasch model - Rumtini; Fauzan, Akhmad; Suwondo, Tirto; Putra, I Ketut Sudharma; Tama, I Wayan; Herlinawati; Sundari, Komang Nelly; Astuti, Marhanani Tri; Rema, I Nyoman; Setiawan, Budiana; Mardiyono; Pamungkas, Onok Yayang (Research Journal in Advanced Humanities, 2026)
The background of this research arises from the reality that in many multilingual countries, governments mandate the use of national languages in official communication, yet compliance at the local bureaucratic level is often inconsistent. Indonesia represents an important case because, although a strong legal foundation exists, everyday practices reveal significant variation. Previous studies rarely examined institutional compliance using rigorous measurement. This research fills that gap by applying the Rasch model to analyze language compliance behavior within bureaucratic settings and to explore organizational mechanisms that support or weaken compliance in multilingual governance. The study employed a survey of 395 civil servants from ministries, provincial governments, cities/districts, and universities across 18 provinces. The 30-item instrument was calibrated with the Rasch model, positioning respondents and items on a common logit scale. Results showed high reliability (Person = 0.87; Item = 0.96), good model fit, and invariance between groups based on DIF analysis. ANOVA indicated no significant compliance differences by education, employment status, or tenure, suggesting that organizational norms and ideologies matter more than individual demographics. Substantively, findings confirm that bureaucratic language compliance is shaped by organizational culture and enforcement mechanisms rather than personal traits. Methodologically, this research demonstrates the Rasch model’s value for producing valid, reliable, and bias-free measurements, supporting cross-group comparison and long-term monitoring.